Many solutions

The positive integer-valued function f ( n ) f(n) satisfies f ( f ( n ) ) = 4 n f(f(n))=4n and f ( n + 1 ) > f ( n ) > 0 f(n+1)>f(n)>0 for all positive integers n n . Let N N be the number of possible 64-tuples ( f ( 1 ) , f ( 2 ) , , f ( 64 ) ) (f(1),f(2),\cdots,f(64)) . Find N N mod 1000.


The answer is 779.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Bob Smith
Dec 29, 2013

Let the number of possible 2 k 2^k -tuples be denoted as F ( k ) F(k) .

First, we may conclude that f(1)=2. Clearly f(1) is not 1 and it cannot be 3 (or else f(3)=4 leading to bounding problems). Thus it follows that f ( 2 k ) = 2 k + 1 f(2^k)=2^{k+1} .

From here, casework on f(3). It is either 5, 6, or 7. (7 results in a symmetric case with 5.)

If f(3)=5 it follows that f(5)=12. Then f(6),f(7) must be the pairs (13,14), (13,15), or (14,15). Either way, there is one gap.

We will show that the other thing doesn't matter with a small lemma.

Lemma: if f(a)=b and f(a+1)=b+1 then it follows that f(x) is fixed on all intervals [ 2 k a , 2 k ( a + 1 ) ] [2^ka,2^k(a+1)] and [ 2 k b , 2 k ( b + 1 ) ] [2^kb,2^k(b+1)] .

Proof: Induction. f(b)=4a, f(b+1)=4a+4, f(4a)=4b, f(4a+4)=4b+4 and tight bounding takes care of the rest. (f(4a+1)=4b+1 and so forth)

So all that remains is a gap of 2 somewhere. Let's say it's (13,14). Then f(14)=28 and f(16)=32. We now have a gap of 4, for f(15). It has 3 options, 29, 30, 31. So this can be recursed to before. There are 6 ways this happens (2 ways for f(3) = 5,7; 3 ways for our choice of f(6), f(7) or f(5), f(6).)

If f(3)=6 it follows that f(6)=12. Importantly, f(5) and f(7) have three options. They exactly mirror the choice we had for f(3). Our choices for f(5), f(7) are independent so we square F(n-1).

So our recurrence is F ( n ) = F ( n 1 ) 2 + 6 F ( n 2 ) F(n)=F(n-1)^2+6F(n-2) , with initial conditions F(1)=1 and F(2)=3. We can easily evaluate F(6) mod 1000 to get 779.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...